Location of Interface Bose-Einstein Condensate Mixtures in Semi-infinite Space under Neumann Boundary Condition - Quyet, Hoang Van (VNU Journal of Science: Mathematics - Physics; Vol 38 No 2DO - 10.25073/2588-1124/vnumap.4703, 2022)
The location of interface plays a pivotal role in studying on wetting phase transition of Bose-Einstein condensates (BECs) mixture. Beside parameters of system, the position of the interface depends on the applied boundary condition. Using double-parabola approximation (DPA), we consider the dependence of position of interface on parameters in semi-infinite space under Neumann boundary condition.